PEMENUHAN HAK-HAK PEKERJA WAKTU TERTENTU PADA PT. WIRATAMA JAYA PERKASA DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Frisri, Alika Nanda; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Fulfillment of certain workers' rights at PT. Wiratama Jaya Perkasa which is not implemented is aform of violation against the applicable law according to the law number 13 of 2003 on employmentArticle 78 has clearly stated that